Every home a fortress: the fallout shelter father in Cold War America - Bishop, Tom (2017)
During the nuclear crisis years of 1958 to 1961, millions of U.S. citizens were instructed by their federal government that the best chance of surviving a direct nuclear confrontation with the Soviet Union resided in converting their backyards or basements into family fallout shelters. Directing their policies towards middle-class suburban America, civil defence policymakers asked citizens to realign their lives and family relationships in accordance with a new doctrine of ‘do-it-yourself’ survival, stating that middle-class suburban fathers had the capacity and resources to protect both themselves and their families from the worst possible manmade disaster. “Every Home a Fortress: The Fallout Shelter Father in Cold War America” is the first historical study of fatherhood and the family fallout shelter during the early Cold War. Focusing specifically on the cultural and political representations of fatherhood and masculinity in the formation of and public reaction to the doctrine of civil defence, this project examines the tension between the politics of ‘do-it-yourself’ survival and the lived reality. The process and practice of fallout shelter construction represented an almost unprecedented level of state penetration into the private sphere. Yet, as the ideal of shelter fatherhood permeated society, a widening gap emerged between the political rhetoric of civil defence and the everyday experience of the ordinary Americans facing the prospect of building a family fallout shelter and surviving the next war. Each chapter of this thesis explores the lived reality of civil defence, highlighting the ways in which U.S. fathers interpreted and reinterpreted the act of private shelter construction. Rather than fostering one singular politicised vision of Cold War fatherhood, this thesis argues that fallout shelters brought to the surface a variety of interlinked visions of Cold War fatherhood, rooted in narratives of domesticity, militarism, and survivalism. Central to these narratives of masculinity was the private fallout shelter itself, a malleable Cold War space that inspired a new national discourse around notions of nationhood, domestic duty, and collective assumptions of what it meant to be a father in the nuclear age.